Pharmacological Characterization of Toludesvenlafaxine as a Triple Reuptake Inhibitor - Zhu, Haibo; Wang, Wenyan; Sha, Chunjie; Guo, Wei; Li, Chunmei; Zhao, Fengjuan; Wang, Hongbo; Jiang, Wanglin; Tian, Jingwei (Frontiers in Pharmacology, 2021)
Toludesvenlafaxine hydrochloride dihydrate is a novel chemical entity and a potential triple monoamine reuptake inhibitor. This study characterized the in vitro triple reuptake inhibition activity, antidepressant-like activity in animals, and pharmacokinetic profiles in rats of toludesvenlafaxine. Binding affinity was determined using human serotonin transporter (SERT) protein, norepinephrine transporter (NET) protein and dopamine transporter (DAT) protein, and the reuptake inhibition was determined using Chinese hamster ovary cells expressing human SERT, NET and DAT. The antidepressant-like activity was examined in rat chronic unpredictable mild stress model and olfactory bulbectomized model. In rats, the tissue distribution and pharmacokinetic parameters were determined. Toludesvenlafaxine had high binding affinity on SERT, NET and DAT, and significantly inhibited the reuptake of serotonin (IC50 =31.4 ± 0.4 nM), norepinephrine (IC50 =586.7 ± 83.6 nM) and dopamine (IC50 = 733.2 ± 10.3 nM) in vitro. Toludesvenlafaxine demonstrated significant antidepressant-like effects in rat models at 8-16 mg/kg. In addition, toludesvenlafaxine significantly reduced serum corticosterone and significantly increased testosterone levels in rats. Toludesvenlafaxine was quickly absorbed and converted to O-desvenlafaxine（ODV) after oral administration, both of which were selectively distributed into the hypothalamus with high concentration. Plasma ODV exposure was proportionally related to the doses after oral dosing. These results suggest that toludesvenlafaxine is a triple reuptake inhibitor with relatively fast-acting antidepressant-like activity and improvedgood therapeutic profile including improvement of anhedonia and sexual function.